The Th1/Tfh-like biased responses elicited by the rASP-1 innate adjuvant are dependent on TRIF and Type I IFN receptor pathways - George, Parakkal Jovvian; Marches, Radu; Nehar-Belaid, Djamel; Banchereau, Jacques; Lustigman, Sara (Frontiers in Immunology, 2022)
Ov-ASP-1 (rASP-1), a parasite-derived protein secreted by the helminth Onchocerca volvulus, is an adjuvant which enhances the potency of the influenza trivalent vaccine (IIV3), even when used with 40-fold less IIV3. This study is aimed to provide a deeper insight into the molecular networks that underline the adjuvanticity of rASP-1. Here we show that rASP-1 stimulates mouse CD11c+ bone marrow-derived dendritic (BMDCs) to secrete elevated levels of IL-12p40, TNF-α, IP-10 and IFN-β in a TRIF-dependent but MyD88-independent manner. rASP-1-activated BMDCs promoted the differentiation of naïve CD4+ T cells into Th1 cells (IFN-γ+) that was TRIF- and type I interferon receptor (IFNAR)-dependent, and into Tfh-like cells (IL21+) and Tfh1 (IFN-γ+ IL21+) that were TRIF-, MyD88- and IFNAR-dependent. rASP-1-activated BMDCs promoted the differentiation of naïve CD4+ T cells into Th17 (IL-17+) cells only when the MyD88 pathway was inhibited. Importantly, rASP-1-activated human blood cDCs expressed upregulated genes that are associated with DC maturation, type I IFN and type II IFN signaling, as well as TLR4-TRIF dependent signaling. These activated cDCs promoted the differentiation of naïve human CD4+ T cells into Th1, Tfh-like and Th17 cells. Our data thus confirms that the rASP-1 is a potent innate adjuvant that polarizes the adaptive T cell responses to Th1/Tfh1 in both mouse and human DCs. Notably, the rASP-1-adjuvanted IIV3 vaccine elicited protection of mice from a lethal H1N1 infection that is also dependent on the TLR4-TRIF axis and IFNAR signaling pathway, as well as on its ability to induce anti-IIV3 antibody production.